Analisa Pengaruh Tekanan Air Terhadap Kinerja PLTMH dengan Menggunakan Turbin Archimedes Screw - Putra, I Gede Widnyana; Weking, Antonius Ibi; Jasa, Lie (Majalah Ilmiah Teknologi Elektro; Vol 17 No 3 (2018): (September - Desember) Majalah Ilmiah Teknologi Elektro, 2018)
The Microhydro Power Plant (MHP) is a small-scale power plant that uses hydropower. The most important component in a microhydro power plant is a turbine. The turbine used in this MHP model is the Archimedes screw turbine. In this research will discuss about the effect of water pressure on the rotation produced by Archimedes screw turbine so that it can be seen voltage, current, generated power by generator, torque and efficiency in modeling of MHP. Changes in water pressure given at 4 psi, 8 psi, 12 psi, 16 psi, 20 psi, and 24 psi. The highest measurement results are obtained at 24 psi water pressure, where the voltage, current, and generator output power is 85.8 Volt, 0.1963 Ampere and 16.85 Watt. For the rotation speed of the generator at 24 psi pressure is equal to 4582 rpm, while the speed of turbine rotation produced at 24 psi this pressure is equal to 383 rpm before coupled with generator and 222 rpm after coupled with generator. The torque and efficiency produced at 24 psi pressure are 0.73 Nm and 18.1%.